If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 2x + 17 Reorder the terms: 7 = 17 + 2x Solving 7 = 17 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7 + -2x = 17 + 2x + -2x Combine like terms: 2x + -2x = 0 7 + -2x = 17 + 0 7 + -2x = 17 Add '-7' to each side of the equation. 7 + -7 + -2x = 17 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = 17 + -7 -2x = 17 + -7 Combine like terms: 17 + -7 = 10 -2x = 10 Divide each side by '-2'. x = -5 Simplifying x = -5
| 4n^2-7n=2 | | -n+3n=6n+16 | | 3-2*-7=17 | | -2(y-3)=12 | | 2a^2+8a=-30 | | 12s^3t^3+3s^4t^2= | | 4=5x-24 | | x^2-5x-32=0 | | x=-2y-15 | | In(2x+1)-1=In(x-2) | | 2x^3+3x^2+36x=0 | | -(-2b^2+3)-b(2b-3)-3= | | 35(p-3)=-4 | | -14=10+3x | | -5x+4x+5=48 | | 4y+7=8y-5 | | -32-(-9)= | | 25s^3t^4+5s^4t^3= | | 2d^4=5d | | -9+6x=5x+12 | | (2x-13)+(x+41)+(x)=180 | | 5(5x-2)=-6(x+2) | | 9x=10x+90 | | -56+x=32+5x | | -(7c+18)-2c0= | | 2x+45=-9(x+6) | | -78+4x=42-8x | | -3(2x+4)+1=19 | | -8x-65=103+4x | | 60s=50 | | .03x+.4=8 | | -18-4x=16-6x |